Structure and mechanical properties of near-eutectic refractory Al-Cr-Nb-Ti-Zr high entropy alloys. Issue 1 (January 2021) - Yurchenko, N; Panina, E; Salishchev, G; Stepanov, N
Abstract: In this study, the structure and mechanical properties of the near-eutectic refractory Al24 Cr11 Nb11 Ti37 Zr17, Al20 Cr20 Nb25 Ti25 Zr10, and Al28 Cr15 Nb15 Ti20 Zr22 (at.%) high entropy alloys were investigated. Both the Al24 Cr11 Nb11 Ti37 Zr17 and Al20 Cr20 Nb25 Ti25 Zr10 alloys had a hypoeutectic structure, while the Al28 Cr15 Nb15 Ti20 Zr22 alloy had a hypereutectic one. The proeutectic phase in the Al24 Cr11 Nb11 Ti37 Zr17 and Al20 Cr20 Nb25 Ti25 Zr10 alloys was the ordered B2 phase and in the Al28 Cr15 Nb15 Ti20 Zr22 alloy – the C14 Laves phase. In all three alloys, the eutectic regions possessed a fine lamellar structure composed of a mixture of the C14 Laves and B2 phases. The densities of the alloys were 5.20-5.89 g/cm 3 . The Al24 Cr11 Nb11 Ti37 Zr17 and Al28 Cr15 Nb15 Ti20 Zr22 alloys were extremely brittle at 22°C, while the Al20 Cr20 Nb25 Ti25 Zr10 alloy showed some ductility (ε = 0.7%) and high yield strength of 1830 MPa. At 800°C, all alloys became ductile. The highest yield strength (1010 MPa) was demonstrated by the Al20 Cr20 Nb25 Ti25 Zr10 alloy and the lowest one (235 MPa) – by the Al24 Cr11 Nb11 Ti37 Zr17 alloy. The comparison between the experimental as-solidified structures and the CALPHAD predictions was made.